Developing Flipbooks and Wordwall-Assisted Digital Media for Teaching Procedural Writing in Elementary Schools - Cerianing Putri Pratiwi; Cintya Nurika Irma; Afrilia Bayu Ivanka (LP. Ma'arif Janggan Magetan, 2024)
This book is based on the theory of constructivism that allows students to build their knowledge through fun and interactive interactions. Flipbooks make it easy to present material with various multimedia elements, while wordwall provides interesting wordplay in writing procedural texts so that it is an easy learning support tool. The purpose of this research is to find out the development of flipbook-based digital books with the help of wordwall for learning to write procedural texts. This research method is development research or R and D using ADDIE design. ADDIE's design steps are Analysis, Design, Development, Implementation, Evaluation. The subjects in this study are teachers and 5th grade elementary school students in Madiun Regency, which totals 5 teachers and 87 students. Data collection techniques using observation and questionnaires. Additional statistical analysis To strengthen the quantitative analysis, a descriptive statistical test was conducted in the form of calculating the average value (mean), standard deviation, minimum, and maximum of the user assessment results. Instrument Validity and Reliability. The questionnaire instrument was validated by two experts, namely a material expert and a media expert, to measure content validityThe results of the study show that the development of digital books is developed according to the needs of teachers and students. Flipbook-based digital books are declared feasible for learning to write procedural texts. With this, it is hoped that it can make students understand more deeply the procedural text material with a fun learning experience.